Best practices for urban local food entrepreneurs and building regional Extension networks - Julie Garden-Robinson; Rebecca West; Londa Nwadike; Karen Blakeslee; Shannon M. Coleman (Urban Food Systems Symposium, 2022)
Interest in local foods production in the urban environment has been steadily increasing in North Dakota and the surrounding region. Food entrepreneurs are seeking safe and reliable ways to grow, create, and market their fresh or freshly preserved products. Urban consumers are demanding local foods and food products that are fresh and safe. As an increasing number of producers and vendors enter farmers markets and other local food sales channels, these growing small businesses need technical assistance for safe food handling and marketing in the changing world of pandemics and supply chain issues. Although some basic practices, such as hand washing, have been encouraged for decades, the pandemic has shown that they are in constant need of reinforcement. Regulations for small-scale food entrepreneurs vary widely from state to state and can be confusing for both entrepreneurs and consumers. This lack of clarity is an ongoing issue, so a best practices document was created and disseminated throughout the North Central Region. The North Central Food Safety Extension Network (NCFSEN) has been building a coalition of Extension food safety professionals in our region since 2016. We have implemented several activities together, including monthly meetings, building relationships with industry professionals, developing educational materials, and creating a program evaluation tool for our region. Our network also has been working steadily to help other regions establish their own Extension coalitions to better serve their constituents as developed around a particular topic, such as food safety in our case. To that end, we have assembled best practices for creating regional Extension networks. The following elements was presented at the conference: 1) background of cottage foods in our region, pre- and post-pandemic; 2) best practices for local food entrepreneurs, including the relevance of “best practices” in view of varying state laws and regulations, health and hygiene policy for employees, volunteers, and family members, market day preparations and contingencies, creating, labeling, and sampling value-added food products; 3) evolving practices for pandemic circumstances in urban markets; 4) building regional Extension coalitions to better serve local constituencies; and 5) best practices for implementing your own regional Extension network, including benefits of regional collaboration, organization, communication, and setting goals.
Keywords: collaboration; cottage; farmers; markets; pandemic